Whole genome sequencing and in vitro splice assays reveal genetic causes for inherited retinal diseases - Farrar, Gwyneth (My University, 2021)
Inherited retinal diseases (IRDs) are a major cause of visual impairment. These clinically heterogeneous disorders are caused by pathogenic variants in more than 270 genes. As 30–40% of cases remain genetically unexplained following conventional genetic testing, we aimed to obtain a genetic diagnosis in an IRD cohort in which the genetic cause was not found using whole-exome sequencing or targeted capture sequencing. We performed whole-genome sequencing (WGS) to identify causative variants in 100 unresolved cases. After initial prioritization, we performed an in-depth interrogation of all noncoding and structural variants in genes when one candidate variant was detected. In addition, functional analysis of putative splice-altering variants was performed using in vitro splice assays. We identified the genetic cause of the disease in 24 patients. Causative coding variants were observed in genes such as ATXN7, CEP78, EYS, FAM161A, and HGSNAT. Gene disrupting structural variants were also detected in ATXN7, PRPF31, and RPGRIP1. In 14 monoallelic cases, we prioritized candidate noncanonical splice sites or deep-intronic variants that were predicted to disrupt the splicing process based on in silico analyses. Of these, seven cases were resolved as they carried pathogenic splice defects. WGS is a powerful tool to identify causative variants residing outside coding regions or heterozygous structural variants. This approach was most efficient in cases with a distinct clinical diagnosis. In addition, in vitro splice assays provide important evidence of the pathogenicity of rare variants.
Keywords: Inherited retinal diseases (IRDs); visual impairment; clinically heterogeneous disorders